The Influence of Regional Government and Community Participation on the Development of Spiritual Tourism in Pante Makasar, Timor-Leste - Cevat Tosun; Jacinto Colo; Helio Brites da Silva (International Journal of Home Economics, Hospitality and Allied Research, 2025)
This study examines the role of government and community participation in the development of spiritual tourism in Pante Makassar, Oe-Cusse Municipality, Timor-Leste. Utilizing a quantitative research approach, the sample consisted of 331 participants, and data analysis was carried out using multiple regression analysis in SPSS 29 software. The results demonstrate significant direct positive impacts of community participation and government involvement on the development of spiritual tourism. In light of the findings, the study offers recommendations to local government authorities and the broader community to promote further the implementation of spiritual tourism values. By leveraging its spiritual importance to attract more visitors, the region stands to benefit economically, providing additional income for both the community and the nation